2020
DOI: 10.15244/pjoes/114233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Activity on Surface Water Quality in Moravian Karst

Abstract: Human activities, population growth and settlements pose a threat of degradation for the natural environment and especially for karst water [1, 2]. Water is a key factor in the formation and occurrence of karst phenomena. A number of surface watercourses flow to the karst areas from the non-protected areas. These watercourses almost instantly disappear into the underground at the geological boundary of the karst area. The hydrological regime of these watercourses in the karst area is very complicated. Undergro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…This ability has also recently been confirmed for other streams in the Moravian Karst (Malá et al 2017) and in Croatian karst watercourses (Cukrov et al 2008). The length of the watercourse from the pollution source to the location where the stream is swallowed into the karst underground plays a significant role in its self-purification (Hübelová et al 2020). This was confirmed by our results, which also showed that the land use in the immediate vicinity of the stream strongly affects its self-cleaning ability.…”
Section: Self-purifying Abilitysupporting
confidence: 89%
See 2 more Smart Citations
“…This ability has also recently been confirmed for other streams in the Moravian Karst (Malá et al 2017) and in Croatian karst watercourses (Cukrov et al 2008). The length of the watercourse from the pollution source to the location where the stream is swallowed into the karst underground plays a significant role in its self-purification (Hübelová et al 2020). This was confirmed by our results, which also showed that the land use in the immediate vicinity of the stream strongly affects its self-cleaning ability.…”
Section: Self-purifying Abilitysupporting
confidence: 89%
“…At this stage of their life cycle, the demands of such people in terms of water sources and wastewater management are the highest of any members of the population (Pavlík et al 2017). The current technical infrastructure (especially the sewer system and wastewater treatment plants-WWTPs) of municipalities is often not sufficient to respond to the consequences of the current population growth (Hübelová et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in impervious surface area and the high pollution caused by urban industry and living have deepened the concentration of WQ pollutants in urban areas and become the main source of pollution output in the region. The second major pollution source is cultivated land [15]. Due to the increased use of cultivated land by human activities, a large number of pesticides and chemical fertilizers are applied to farmland, which increases chemical elements in a regional farmland and exacerbates the deposition of pollutants.…”
Section: Impact Of Lulc-landscape Types On Wq In Coastal Wetlandsmentioning
confidence: 99%
“…Intense agricultural activity and rapid urbanization have severely accelerated the deterioration of WQ [14]. Intensive and extensive farming, especially the use of fertilizers, has a greater impact on WQ [15]. Chemical fertilizers enter surface water through runoff, which lead to a significant positive correlation between agricultural land coverage and water pollution.…”
Section: Introductionmentioning
confidence: 99%